2020
DOI: 10.1186/s40529-020-00302-5
|View full text |Cite
|
Sign up to set email alerts
|

Roles of stay-green (SGR) homologs during chlorophyll degradation in green plants

Abstract: Chlorophyll (Chl) degradation is one of the most obvious signs of leaf senescence and fruit ripening. Stay-green (SGR) homologs that can remove magnesium from Chl a are the most important components in Chl degradation pathway in green plants. SGR homologs are not only universally involved in Chl breakdown during the senescence of green organs, but also play crucial roles in other organs during plant growth and development, such as fruit mature and nodule development. In this review, we focus on the diverse fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
(79 reference statements)
3
24
0
Order By: Relevance
“…The developmental processes of fleshy fruits include cell division and expansion during fruit growth, followed by chlorophyll degradation, cell wall softening, and changes to phenylpropanoid, flavonoid, starch/sucrose, and carotenoid metabolism during ripening. These processes are controlled by phytohormones, most notably ethylene in climacteric fruit ripening and ABA in non-climacteric fruit ripening, as well as ABA-ethylene interactions in both types of fruit ( Forlani et al, 2019 ; García-Gómez et al, 2020 ; Jiao et al, 2020 ).…”
Section: An Integrated Comprehensive Understanding Of Aba In Fleshy mentioning
confidence: 99%
“…The developmental processes of fleshy fruits include cell division and expansion during fruit growth, followed by chlorophyll degradation, cell wall softening, and changes to phenylpropanoid, flavonoid, starch/sucrose, and carotenoid metabolism during ripening. These processes are controlled by phytohormones, most notably ethylene in climacteric fruit ripening and ABA in non-climacteric fruit ripening, as well as ABA-ethylene interactions in both types of fruit ( Forlani et al, 2019 ; García-Gómez et al, 2020 ; Jiao et al, 2020 ).…”
Section: An Integrated Comprehensive Understanding Of Aba In Fleshy mentioning
confidence: 99%
“…Stay-green (SGR) genes encode magnesium dechelatase, and are involved in chlorophyll (Chl) degradation. Stay-green (SGR) homologs remove magnesium from Chl a, which is one of the most important components in the Chl degradation pathway in plants [53][54][55]. Under high-temperature conditions, accumulation of sugars in the peel was induced in bananas, and these sugars regulated Chl degradation through SGR proteins [56].…”
Section: Response To Heat Stressmentioning
confidence: 99%
“…The amino acid cysteine plays a crucial role in the formation of crosslinking or intramolecular regulation during the aging process. It also causes the formation of ROS, which leads to the formation of dimers or polymers of the SGR gene resulting in the acceleration of chlorophyll degradation and detoxification during the aging process (Jiao et al, 2020). Jiang et al (2011) reported that overexpression of SGR (Ov-SGR) resulted in the generation of singlet oxygen and ROS and caused cell death in rice sprouts.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between SGR and SGRL proteins lies in the cysteine motif present in the C-terminal section. The structure of the SGR protein consists of three domains, including the highly-conserved SGR domain, chloroplast transit peptide, and the variable C-terminal region (Aubry et al, 2008;Jiao et al, 2020). Other studies reported that SGR or NON-YELLOWING 1 (NYE1), SGR2 (NYE2), and SGRL exhibited as key regulators of chlorophyll degradation in Arabidopsis and rice plants, causing loss of green leaf pigment (senescence) (Jiang et al, 2007;Park et al, 2007;Rong et al, 2013;Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%